2015
DOI: 10.1371/journal.pone.0122647
|View full text |Cite
|
Sign up to set email alerts
|

Robertsonian Translocations: An Overview of 872 Robertsonian Translocations Identified in a Diagnostic Laboratory in China

Abstract: Robertsonian translocations (ROBs) have an estimated incidence rate of 1/1000 births, making this type of rearrangement the most common structural chromosomal abnormalities seen in the general population. In this study, we reports 872 cases of ROBs from 205,001 specimens karyotyped postnatally in a single accredited laboratory in China, including 583 balanced ROBs, 264 unbalanced ROBs, 9 mosaic ROBs, and 18 complex ROBs. Ninety-three percent of the balanced ROBs observed were adults with infertility, miscarria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 35 publications
5
29
1
2
Order By: Relevance
“…Robertsonian translocations are one of the most frequent reorganizations in humans. Most of the cases analyzed correspond to rearrangements with chromosomes from the D-group (chromosomes 13, 14 and 15), whereas some rare Robertsonian translocations are scarcely found in the literature, mainly those with both chromosomes from the G-group (chromosomes 21 and 22) and those involving chromosomes from both groups (D;G translocations) [10,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Robertsonian translocations are one of the most frequent reorganizations in humans. Most of the cases analyzed correspond to rearrangements with chromosomes from the D-group (chromosomes 13, 14 and 15), whereas some rare Robertsonian translocations are scarcely found in the literature, mainly those with both chromosomes from the G-group (chromosomes 21 and 22) and those involving chromosomes from both groups (D;G translocations) [10,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study from Chinese population on 872 cases of Robertsonian translocations revealed 93% of the balanced translocations were having problem of infertility, miscarriage, or offspring(s) with known chromosomal abnormalities [13]. In our study, both the carrier of [rob t (13;14)], i.e., father in case-1 and mother in case-2 ( Figures 1A and 1B) were phenotypically normal (except soft soft sub-mucous cleft palate with father in case-1).…”
Section: Discussionmentioning
confidence: 99%
“…Translocations Couple with reproductive disorders (Tables S5, S6) Single cases tested for various reasons (Table S9) Consecutive patients from a genetic unit [44] Total Table 5. Spectrum of homologous translocations and sex ratio among carriers, updated from [43].…”
Section: Rates and Spectrum Of Ht In Asymptomatic Carriersmentioning
confidence: 99%